1981
DOI: 10.1017/s0003356100027203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unwilted and wilted silages and hay, supplemented with different amounts of concentrate, on live-weight gain of calves

Abstract: Three experiments were carried out to investigate the effect of different forage types on the performance of male British Friesian calves up to 6 months of age. Unwilted and wilted silages were compared in all experiments, and in experiment 1 hay was also compared with the two silages. All the forages were compared at different levels of concentrate supplementation ranging, in different experiments, from none to ad libitum.Calves fed wilted silage consumed 490, 90 and 200g/kg more forage dry matter respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Krosowski and KTosowska (1984) and KTosowski et al (1988) reported that the faster the animals' growth as affected by feeding, the larger the fibre diameter and higher the percentage of FTG fibers. In growing calves reared on hayfree low-concentrate diets based on grass silage, satisfactory gains have been reported (Marsh, 1975(Marsh, , 1976Bartholomew et al, 1981;Bidwell-Porgbska et al, 1987;Piotrowski et al, 1988) (Ziegan, 1979 (Brooke, 1970) In the younger calves the intake of crude protein (CP) and gross energy (GE) was also slightly higher in the SD fed group. In the older animals the daily intake of GE was considerably higher, while the intake of CP was lower in the SD than in the HD fed group (table I).…”
mentioning
confidence: 97%
“…Krosowski and KTosowska (1984) and KTosowski et al (1988) reported that the faster the animals' growth as affected by feeding, the larger the fibre diameter and higher the percentage of FTG fibers. In growing calves reared on hayfree low-concentrate diets based on grass silage, satisfactory gains have been reported (Marsh, 1975(Marsh, , 1976Bartholomew et al, 1981;Bidwell-Porgbska et al, 1987;Piotrowski et al, 1988) (Ziegan, 1979 (Brooke, 1970) In the younger calves the intake of crude protein (CP) and gross energy (GE) was also slightly higher in the SD fed group. In the older animals the daily intake of GE was considerably higher, while the intake of CP was lower in the SD than in the HD fed group (table I).…”
mentioning
confidence: 97%